Descrição de sete novas espécies e dois novos gêneros de Physocypria sensu latu (Crustacea, Ostracoda) de planícies de inundação brasileiras. - Almeida, Nadiny Martins de (2022)
We describe seven new species of Physocypria sensu latu from three of the main Brazilian floodplains: Gen. 1 spec. A gen. et spec. nov. and Gen. 1 spec. B gen. et spec. nov. from the Upper Paraná River floodplain and the South Matogrossense Pantanal, Gen. 2 spec. C gen. et spec. nov., Gen. 1 spec. D gen. et spec. nov. and Gen. 2 spec. E gen. et spec. nov. from the South Matogrossense Pantanal only and Gen. 1 spec. F gen. et spec. nov. and Gen. 1 spec. G gen. et spec. nov. only from the Amazon River floodplain. All new species here described were found in sexual populations. Generally, the new species have a short and suboval carapace, with the left valve overlapping the right valve on all sides, except for the dorsal side in some species. The morphology of hemipenis and prehensile palps, together with the shape of the valves, were most important to distinguish the species. However, several other morphological characters from limb chaetotaxy are discussed, e.g., the absence in all new species of the short accompanying seta of the five natatory setae on antenna; the presence in all new species of a long seta next to the two a-seta on the first thoracopod and the presence/absence or length of specific setae on second and third thoracopod. We discuss the taxonomic position of the seven new species by evaluating the validity of extant genera, especially of Keysercypria Karanovic, 2011, and foreshadow that our seven new species represent two new genera of Cyclocypridinae.